1998
DOI: 10.1080/03601239809373151
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of carbosulfan by carbosulfan - and carbofuran - retreated rice soil suspension

Abstract: The role of microorganisms in the degradation of carbosulfan (2,3-dihydro-2,2-dimethyl-7-benzofuranyl-(di-n-butyl)-aminosulfenyl++ + methyl carbamate), an analogue of carbofuran (2,3-dihydro-2,2-dimethyl-7-benzofuranyl-N-methyl carbamate) was studied by selective enrichment of microorganisms degrading either or both insecticides by repeated application of the insecticides, individually or in combination to flooded soil. Soil suspension from the pots treated with carbosulfan and carbofuran, individually or in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Many authors, in fact, report the capability of soil microrganisms to use the carbamate insecticides (aldicarb and carbofuran and some metabolites) as a source of carbon and nitrogen for growth (Ou et al, 1988;Baron and Merriam, 1988;Rasul Chaudry and Ali, 1988;Sahoo et al, 1998;Salama, 1998). Since in the case of hydroxycarbofuran and ketocarbofuran the differences in bacterial numbers between treated soils and controls are not significant, the degradation might be due to both chemical and co-metabolic processes.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Many authors, in fact, report the capability of soil microrganisms to use the carbamate insecticides (aldicarb and carbofuran and some metabolites) as a source of carbon and nitrogen for growth (Ou et al, 1988;Baron and Merriam, 1988;Rasul Chaudry and Ali, 1988;Sahoo et al, 1998;Salama, 1998). Since in the case of hydroxycarbofuran and ketocarbofuran the differences in bacterial numbers between treated soils and controls are not significant, the degradation might be due to both chemical and co-metabolic processes.…”
mentioning
confidence: 91%
“…The degradation of these parent compounds and of their main metabolites has been studied in extensively (Kale et al, 2001;Kazumi and Capone, 1995) and several soil microorganisms have been reported to transform aldicarb and carbofuran Trabue et al, 1997;Sahoo et al, 1998;Salama, 1998) to their main metabolites; however, the biochemical pathways regarding the complete mineralization of the transformation products are still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated biotransformation has also been evinced for aldicarb (Read, 1987;Suett & Jukes, 1988), carbofuran (Harris et al, 1984;Read, 1986;Suett, 1986Suett, , 1987Racke & Coats, 1988b, Morel-Chevillet et al, 1996Karpouzas et al, 2000a), carbosulfan (Sahoo et al, 1990(Sahoo et al, , 1998, cadusafos (Anderson et al, 1998;Karpouzas et al, 2004), ethoprophos and oxamyl (Smelt et al, 1987;Karpouzas et al, 1999Karpouzas et al, , 2000b, fenamiphos (Ou, 1991;Chung & Ou, 1996;Pattison et al, 2000) and terbufos (Felsot, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of carbamates and their transformation products (TPs) in fruits is, presently, an important concern because some processes, such as hydrolysis, biodegradation, oxidation, photolysis, etc., implicated in their disappearance can lead to compounds that are more toxic than the parent pesticides 1–4. A typical example of this problem is carbosulfan, which degrades to carbofuran and 3‐hydroxycarbofuran; the former compound is more toxic than carbosulfan, while the metabolites are rather persistent 5, 6. This pesticide has a temporary acceptable daily intake (ADI) of 0.01 mg kg −1 body weight (bw) and a maximum residue limit (MRL) of 0.05 mg kg −1 for the sum of carbosulfan, carbofuran and 3‐hydroxycarbofuran in citrus fruits 7, 8…”
mentioning
confidence: 99%